Resource utilization and outcomes in emergency general surgery during the COVID19 pandemic: An observational cost analysis. - Amelia J Hessheimer; Marta Trapero-Bertran; Alex Borin; Eugenia Butori; Anna Curell; Arlena Sofía Espinoza; Joaquín Jensen; Víctor Turrado; Xavier Morales; Antonio María de Lacy; Constantino Fondevila (PLoS ONE, 2021)
Background Over the course of the COVID19 pandemic, global healthcare delivery has declined. Surgery is one of the most resource-intensive area of medicine; loss of surgical care has had untold health and economic consequences. Herein, we evaluate resource utilization, outcomes, and healthcare costs associated with unplanned surgery admissions during the height of the pandemic in 2020 versus the same period in 2019. Methods Retrospective analysis on patients ≥18 years admitted from the emergency department to General & Digestive and Gastrointestinal Surgery Services between February and May 2019 and 2020 at our center; clinical outcomes and unadjusted and adjusted per-person healthcare costs were analyzed. Results Consults and admissions to surgery declined between February and May 2020 by 37% and 19%, respectively, relative to the same period in 2019, with even greater relative decline during late March and early April. Time between onset of symptoms to diagnosis increased from 2±3 days 2019 to 5±22 days 2020 (P = 0.01). Overall hospital stay was two days less in 2020 (P = 0.19). Complications (Comprehensive Complication Index 10.3±23.7 2019 vs. 13.9±25.5 2020, P = 0.10) and mortality rates (3% vs. 4%, respectively, P = 0.58) did not vary. Mean unadjusted per-person costs for patients in the 2019 and 2020 cohorts were 5,886.72€±12,576.33€ and 5,287.62±7,220.16€, respectively (P = 0.43). Following multivariate analysis, costs remained similar (4,656.89€±390.53€ 2019 vs. 4,938.54±406.55€ 2020, P = 0.28). Conclusions Healthcare delivery and spending for unplanned general surgery admissions declined considerably due to COVID19. These results provide a small yet relevant illustration of clinical and economic ramifications of this healthcare crisis.